Ride a purple pelican - Prelutsky, Jack.; Williams, Garth (New York : Greenwillow Books, 1986)
A collection of short nonsense verses and nursery rhymes.
Children's Catalog (Wilson)
School Library Journal
Horn Book Magazine
3.5
3-6
Keywords: Children's poetry, American; American poetry; Nonsense verses; Nursery rhymes; American poetry; Nonsense verses; Nursery rhymes